2012
DOI: 10.3945/jn.112.166231
|View full text |Cite
|
Sign up to set email alerts
|

Can Nutritional Modulation of Maternal Intestinal Microbiota Influence the Development of the Infant Gastrointestinal Tract?,

Abstract: The gastrointestinal microbiota plays an important role in maintaining host health by preventing the colonization of pathogens, fermenting dietary compounds, and maintaining normal mucosal immunity. Particularly in early life, the composition of the microbiota profoundly influences the development and maturation of the gastrointestinal tract (GIT) mucosa, which may affect health in later life. Therefore, strategies to manipulate the microbiota during infancy may prevent the development of some diseases later i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 128 publications
2
98
1
4
Order By: Relevance
“…If maternal enteric microbiota influence human milk microbiota, and human milk microbes influence colonization and succession of infant enteric microbiota, strategies to adjust maternal gut with selected bacteria (17) should confer benefits to the offspring. The connection between maternal microbiota and milk microbiota is discussed above; the connection between milk microbes and infant gut is addressed below.…”
Section: Defining Human Milk Microbiotamentioning
confidence: 99%
“…If maternal enteric microbiota influence human milk microbiota, and human milk microbes influence colonization and succession of infant enteric microbiota, strategies to adjust maternal gut with selected bacteria (17) should confer benefits to the offspring. The connection between maternal microbiota and milk microbiota is discussed above; the connection between milk microbes and infant gut is addressed below.…”
Section: Defining Human Milk Microbiotamentioning
confidence: 99%
“…As a consequence, the World Health Organization published both new standardized diagnostic approaches toward male factor infertility 11 and standardized techniques of semen analysis. [12][13][14] Furthermore, the introduction of assisted reproductive techniques, such as in vitro fertilization and intracytoplasmic sperm injection, 15 revolutionized reproductive medicine, revealing the role of the male factor in couple infertility. 16 However, in the last decade, increasing concerns about the ethics, economics, and side effects of assisted reproductive techniques have been raised worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…31 These positive effects were more evident in women who had vaginal delivery than in those undergoing a Cesarean section. In addition, in a recent review, Thum and colleagues 32 reported that maternal supplementation during pregnancy with probiotics, prebiotics and synbiotics had several positive effects (e.g., prevention of atopic diseases, improvements in glucose homeostasis, reduction of gestational diabetes and immune and inflammatory diseases, increase in the concentration of available folate).…”
Section: Possible Interventions To Modify Microbiotamentioning
confidence: 99%